Post-war Civil War Propaganda Techniques and Media Spins in Nigeria and Journalism Practice (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
In public relations and political communication, a spin is a form of propaganda achieved through knowingly presenting a biased interpretation of an event or issues. It is also the act of presenting narratives to influence public opinion about events, people or and ideas. In war time, various forms of spins are employed by antagonists to wear out the opponents and push their brigades to victory. During the Nigerian civil war, quite a number of these spins were dominant – for example GOWON (Go On With One Nigeria); “On Aburi We Stand”, “O Le Ku Ija Ore”. Post-war years presented different spins and fifty years after the war, different spins continue to push emerging narratives (e.g. “marginalization”, “restructuring”). This paper investigates and analyzes the different propaganda techniques and spins in the narratives of the Nigerian civil in the past five years through a content analysis of three national newspapers: The Nigerian Tribune, Daily Trust and Sun Newspapers. Findings confirm that propaganda and spins are not limited to war time, but are actively deployed in peace time. This development places additional challenge on journalists to uphold the canons of balance, truth and fairness in reporting sensitive national issues. The authors extend postulations that propaganda techniques, generally considered to be limited to war situations, are increasingly being used in post-war situations. Specifically, they highlight that journalists are becoming more susceptible to propaganda spins and this could affect the level of their compliance to the ethics of journalism.